Difference in Total Serum Immunoglobulin E Level Among Patients With and Without Intravenous Contrast Media Adverse Reaction on Computed Tomography Scan Examination - Ikhmawati, Yulikha; Zubir, Zuhrial; Daulay, Elvita Rahmi (Talenta Publisher, 2019)
The adverse reaction (AR) to intravenous contrast media (ICM) are relatively common. Various opinions pro-posed in the mechanism of the incidence of ICM AR. Suspected that the role of Immunoglobulin E (IgE) me-diates allergic conditions that are part of the AR. Objective:To determine the difference in total serum IgE level among subjects with and without ICM AR on computed tomography (CT) scan examination. To ob-serve difference in total serum IgE levels in subjects undergoing ICM adverse reaction based on the degree of severity. Method: An analytical study with cross-sectional design of 104 subjects undergoing CT scans with ICM, examined IgE levels before and after ICM was administered, then measured the severity of adverse re-actions of contrast media. Result: In this study, subjects undergoing adverse reactions, prior to administration Iopamidol had a higher mean IgE 1270.79 mg / dl compared with those who having AR 1174.90 mg / dl and after administration of Iopamidol a mean of Ig E is still higher in subjects having AR 1507.96 mg/dl com-pared with those having negative AR that is 1325.88 mg/dl, p = 0.696, statistically, not significant. Mild reac-tions in 40 subjects (38.5%) with cough, nausea, dizziness, itching, and sweating. Conclusion: Increase in total IgE levels in subjects with positive adverse reactions are independent(p=0.696).